ANÁLISIS DE LOS GASES DE COMBUSTIÓN - EL VERDADERO ROL DE LAS PRUEBAS DE TUBO - Fabian Camilo Yatte Garzon; Luis Roberto Oliveros Gómez; Samuel Fernando Muñoz Navarro (Revista Fuentes El Reventón Energético, 2012)
During and after a combustion tube test, when the post-core is disassembly and removed, the produced fluids are amalysed. The emulsions are analyzed by the addition of toluene and centrifugation. Each oil sample is analyzed to determine the viscosity and density. Also, the analysis of the water samples involves measurement of pH, total solids, total carbon and various cations and anions such as sulfates, carbonates, chlorides, magnesium, sodium and potassium. The most important analysis in the tube test is the analysis of gases; this is done for the determination of stoichiometric parameters, involving the understanding of the reactions that occurred in the process. This is done with the help of the results given by chromatography, where the molar compositions of the compounds of the gas produced are determined. These results are processed to calculate the most important variables for evaluating the process. With these variables it is possible to compare tests done in laboratory to determinate whether they are successful or which is the operating temperature range.